SISTEM PAKAR PENENTU KECERDASAN JAMAK PADA ANAK BERBASIS WEB - Rheinhard, Rheinhard; Firdha, Firdha; Aldous, Aldous; RP, Florensa (Teknik dan Ilmu Komputer, 2013)
Multiple Intelligence considers nine aspects of intelligence. It descriptively sees how people use their intelligence to solve problems and produce something. Every child has a variety of intelligences, but one intelligence is the most dominant. Determining a childâs multiple intelligences can be done throughÂ  an expert system. This expert system presents a number of information and determinant test of a childâs multiple intelligence which is web based and can be accessed through a computer browser. This expert system allows each user, especially parents and teachers to recognize the most prominent multiple intelligence of each child through the existing intelligence test. Â Keywords: multiple intelligence, expert system, web